Polysemy and Pun Strategy in Network Discourse - Kendjaeva, Zemfira (The Lingua Spectrum, 2025)
The increasing proliferation of network discourse has spurred innovative humor strategies, such as pun usage based on polysemy. This article investigates the role of polysemous ambiguity in English and Uzbek digital humor, focusing on the construction of pun‑jokes. Drawing on a corpus‑based analysis of English online jokes, which revealed that up to 35.43 % of pun‑jokes hinge on the ambiguity of a single metaphorical word (Mason, 2016), and on qualitative observations of Uzbek TikTok memes, which predominantly exploit phonetic homonymy while increasingly integrating polysemous metaphors for comedic effect, we explore cross‑cultural variations in pun strategies and their cognitive and pragmatic underpinnings.